2017
DOI: 10.5603/cj.a2017.0052
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure: Pilot transcriptomic analysis of cardiac tissue by RNA-sequencing

Abstract: The present findings revealed specific expression pattern of both protein-coding and lncRNAs in HF patients, confirming that new LV myocardial biomarkers could be reliably identified using Next-Generation Sequencing-based approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…In this study, we performed a quantitative meta-analysis of three independent RNA-seq studies using human left ventricle tissues to profile gene expression signatures and identify novel genes associated with DCM. To better integrate the RNA-seq results from different studies, we applied a consistent bioinformatics pipeline (Figure 1) to analyze the raw RNA-seq data (FASTQ files) from the three independent studies in which three different pipelines were used [10][11][12]. Among a total of 58,884 genes used for expression quantification, 789 genes were identified as differentially expressed in meta-analysis including 581 downregulated and 208 upregulated genes ( Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we performed a quantitative meta-analysis of three independent RNA-seq studies using human left ventricle tissues to profile gene expression signatures and identify novel genes associated with DCM. To better integrate the RNA-seq results from different studies, we applied a consistent bioinformatics pipeline (Figure 1) to analyze the raw RNA-seq data (FASTQ files) from the three independent studies in which three different pipelines were used [10][11][12]. Among a total of 58,884 genes used for expression quantification, 789 genes were identified as differentially expressed in meta-analysis including 581 downregulated and 208 upregulated genes ( Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…NCBI GEO [9] database (https://www.ncbi.nlm.nih.gov/geo/) was queried for RNA-seq studies of dilated cardiomyopathy as summarized in Table 1. The clinical information of DCM patients and their controls has been reported in Study_1 [10], Study_2 [11] and Study_3 [12]. Only studies using tissue samples obtained from human left ventricle were included in our meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing (RNA-seq) data, publicly available in the Genotype-Tissue Expression portal (GTEx; https:// gtexportal.org/home/), also support the evidence of exon 5 skipping in human subcutaneous and visceral adipose tissue (SAT and VAT, respectively), as well as in breast and bladder tissue ( Figure S1C). Additionally, the re-analysis of in-house-generated RNA-seq datasets from human primary cells and cell lines (i.e., fibroblasts, heart, liver, peripheral blood mononuclear cells, and papillary thyroid carcinomas; Schiano et al, 2017;Petrizzo et al, 2016;Costa et al, 2015) confirmed exon 5 as the most common splicing event in the PPARG gene ( Figure S1D). Interestingly, RT-PCR assays on different mouse tissues revealed that this alternative splicing event is very common even in murine insulin-sensitive tissues ( Figure 1C).…”
Section: Identification Of a Legitimate Splicing Event In The Pparg Genementioning
confidence: 96%
“…Xie et al [15] indicated that lncRNA HULC can be utilized to diagnose hepatocellular carcinoma. In cardiovascular diseases, lncRNAs have also been verified to be involved in the pathological process of heart failure, myocardial infarction, dilated cardiomyopathy and coronary atherosclerosis [16][17][18][19][20][21][22]. Kumarswamy et al [17], found, with the use of microarray analysis, that lncRNA-LIPCAR was substantially negatively related to left ventricular remodeling; the expression level of LIPCAR was positively associated with mortality of patients with systolic heart failure was also verified.…”
Section: Introductionmentioning
confidence: 92%